Analysis of Religious Character Value In Literacy Programs Based on Critical Pedagogic - Mariana Widjaja; Dinn Wahyudin; Rusman Rusman (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the character values that are instilled through literacy programs implemented at the elementary school level. This analysis is based on a critical pedagogic approach. This study uses content analysis research methods on the literacy program documents of the ministry of education, especially those implemented at the elementary school level. The research findings show that there is integration of instilling character values in students through literacy activities so that students become individual lifelong learners, character values instilled through literacy programs are one way to achieve real educational goals. In addition, based on an analysis with a critical pedagogic approach, the integration of character values in literacy programs is an educational process to make humans become fully human in dealing with the problems they face. It can be concluded that the integration of character values in the literacy program is one of the efforts of the government to strive for humanization of education. Through the integration of these character values, the government can develop the character and manners of students so that they become lifelong learners who have good character.